Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $a,b,c, >0$ be real numbers such that $$\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}\ge3$$

How to prove that :

$$\frac{(ab+b)(2b+1)}{(ab+a)(5b+1)}+\frac{(bc+c)(2c+1)}{(bc+b)(5c+1)}+\frac{(ca+a)(2a+1)}{(ca+c)(5a+1)}\ge\frac{3}{2}$$

share|improve this question
    
I think there is some problem with first and second term. Match them with the pattern of third term. –  Aang Jul 12 '12 at 17:11
    
I don't see any problem. –  Host-website-on-iPage Jul 12 '12 at 17:14
    
The title didn't match the statement in the body. I'll edit. –  Robert Israel Jul 12 '12 at 17:14
    
now it's fine :) –  Aang Jul 12 '12 at 17:19
    
It comes from here fen.bilkent.edu.tr/~cvmath/Problem/problem_2011.htm (April 2011) –  Unoqualunque Sep 2 '12 at 11:06
add comment

2 Answers

I) Let us define for $x\geq 0$ the rational function

$$\tag{1} f(x)~:=~ \frac{(x+1)(x+5)}{x+2}~=~ x+4 - \frac{3}{x+2}~>~0, \qquad x\geq 0. $$

It is not hard to see that $f$ is positive, monotonically increasing

$$\tag{2} f'(x)~=~ 1 + \frac{3}{(x+2)^2}~>~0, \qquad x\geq 0, $$

and concave for $x\geq 0$. The tangent at $x=1$ is above the concave function,

$$\tag{3} f(x) ~\leq~ f(1) +(x-1) f'(1)~=~\frac{4}{3}(x+2), \qquad x\geq 0.$$

II) By going to reciprocal variables OP's inequality (v7) can be written as

$$\tag{4} \forall x,y,z\geq 0:\quad x^2 +y^2 +z^2 \geq 3 \quad\Rightarrow\quad \frac{x+1}{f(y)} + \frac{y+1}{f(z)} + \frac{z+1}{f(x)} ~\stackrel{?}{\geq}~ \frac{3}{2}. $$

III) If we could prove that

$$\tag{5} \forall x,y,z\geq 0:\quad x^2 +y^2 +z^2 \geq 3 \quad\Rightarrow\quad \frac{x+1}{y+2} + \frac{y+1}{z+2} + \frac{z+1}{x+2} ~\stackrel{?}{\geq}~ 2, $$

then eq. (4) would follow from eqs. (3) and (5).

IV) Equation (5) can be rewritten as

$$\tag{6} \forall x,y,z\geq 0:\quad x^2 +y^2 +z^2 \geq 3 \quad\Rightarrow \quad g(x,y,z)~\stackrel{?}{\geq}~ 0, $$

where

$$ g(x,y,z) ~:=~-2(x+2)(y+2)(z+2)+ \sum_{{\rm cycl.}~ x,y,z}(x+1)(x+2)(y+2) $$ $$~=~ -2xyz -4 +\sum_{{\rm cycl.}~ x,y,z}\left(x^2y+2x^2-xy\right)$$ $$ \tag{7} ~=~ 2\underbrace{\left(-xyz+\frac{1}{3}\sum_{{\rm cycl.}~ x,y,z}x^2y\right)}_{\geq 0 ~\text{because of (AG)}.} +\underbrace{\left(-3+\sum_{{\rm cycl.}~ x,y,z}x^2\right)}_{\geq 0}+h(x,y,z), $$

where

$$ \tag{8} h(x,y,z) ~:=~ -1+\sum_{{\rm cycl.}~ x,y,z}\left(\frac{1}{3}x^2y+x^2-xy\right). $$

In equation (7) we have used the inequality of arithmetic and geometric means (AG).

V) If we could prove that

$$\tag{9} \forall x,y,z\geq 0:\quad x^2 +y^2 +z^2 \geq 3 \quad\Rightarrow \quad h(x,y,z)~\stackrel{?}{\geq}~ 0, $$

then eq. (6) would follow from eqs. (7) and (9).

VI) The function $h$ has no internal stationary points because the radial derivative is strictly positive:

$$r \frac{\partial h(x,y,z)}{\partial r} ~=~x \frac{\partial h(x,y,z)}{\partial x}+y \frac{\partial h(x,y,z)}{\partial y}+z \frac{\partial h(x,y,z)}{\partial z}$$ $$\tag{10}~=~\sum_{{\rm cycl.}~ x,y,z}\left(x^2y+2x^2-2xy\right) ~=~\sum_{{\rm cycl.}~ x,y,z}\left(x^2y+(x-y)^2\right)~>0.$$

Thus we may restrict to the sphere $x^2+y^2+z^2=3$ from now on. In other words, if we could prove that $$\tag{11} \forall x,y,z\geq 0:\quad x^2 +y^2 +z^2 = 3 \quad\Rightarrow \quad h(x,y,z)~\stackrel{?}{\geq}~ 0, $$

then eq. (9) would follow.

VII) Let us rewrite

$$\tag{12} h(x,y,z) ~=~ 2 + \underbrace{\left(-3+\sum_{{\rm cycl.}~ x,y,z}x^2\right)}_{= 0} - j(x,y,z), $$

where

$$ \tag{13} j(x,y,z) ~:=~ \sum_{{\rm cycl.}~ x,y,z}k(x)y, $$

and where the concave function $k$ is

$$ \tag{14} k(x) ~:=~ x(1-\frac{x}{3}) $$

with derivative $k'(x) = 1-\frac{2x}{3}$. The tangent at $x=1$ is above the concave function,

$$\tag{15} k(x) ~\leq~ k(1) +(x-1) k'(1)~=~\frac{x+1}{3}.$$

If we could prove that

$$\tag{16} \forall x,y,z\geq 0:\quad x^2 +y^2 +z^2 = 3 \quad\Rightarrow \quad j(x,y,z)~\stackrel{?}{\leq}~ 2, $$

then eq. (11) would follow.

VIII) Proof of eq. (16):

$$\tag{17} j(x,y,z) ~\leq~\frac{1}{3}\sum_{{\rm cycl.}~ x,y,z}(x+1)y ~\leq~2. $$

The first inequality follows from eqs. (13) and (15). The second inequality follows because

$$\tag{18} \sum_{{\rm cycl.}~ x,y,z}xy ~\leq~ \sum_{{\rm cycl.}~ x,y,z}x^2 ~=~3, $$

and because $(x,y,z)=(1,1,1)$ is the maximum point for the function $(x,y,z)\mapsto x+y+z$ on the sphere $x^2+y^2+z^2=3$.

IX) Working backwards through the chain of arguments, we have proven OP's inequality.

share|improve this answer
1  
This is not the shortest proof, but at least it is elementary and correct. –  Qmechanic Jul 20 '12 at 10:08
add comment

Let $a=\frac{1}{x} ,b=\frac{1}{y} ,c=\frac{1}{z} $

$ \frac{(x+1)(y+2)}{(y+1)(y+5)} + \frac{(y+1)(z+2)}{(z+1)(z+5)}+\frac{(z+1)(x+2)}{(x+1)(x+5)} \geq \frac{3}{2} $

note that $\frac{y+2}{(y+1)(y+5)}\ge \frac{3}{4(y+2)} $

then is enough to prove that $\frac{x+1}{y+2} + \frac{y+1}{z+2} + \frac{z+1}{x+2} \geq 2$

by Cauchy-Schwarz

$\frac{x+1}{y+2} + \frac{y+1}{z+2} + \frac{z+1}{x+2} =$

$\frac{(x+1)^2}{ (x+1)(y+2) }+\frac{(y+1)^2}{(y+1)(z+2)}+\frac{(z+1)^2}{(z+1)(x+2)}\geq \frac{((x+1)+(y+1)+(z+1))^2}{(x+1)(y+2) +(y+1)(z+2) +(z+1)(x+2) } \geq 2$

share|improve this answer
    
+1, elegant and correct. –  Qmechanic Jul 20 '12 at 10:11
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.